Simulation Analysis of Regional Temperature Effects and Battery Management Schedules for a Residential‐Scale Vanadium Redox Flow Battery System. Issue 2 (11th April 2014) - Tang, Ao; Skyllas‐Kazacos, Maria
Abstract For all‐vanadium redox flow batteries, prevention of vanadium‐component precipitation and restoration of capacity loss are two critical concerns in battery operation and real applications. Previous studies at the University of New South Wales have demonstrated the usefulness of dynamic modelling in predicting capacity decay and electrolyte temperature variation under specified operating conditions, which can help in the development of advanced flow battery control systems and optimisation of battery design and operation. As an extension of previous modelling studies, this paper aims to explore electrolyte temperature variations associated with different regional temperature effects by using model predictions for a residential‐scale vanadium redox flow battery system designed for peak‐shaving purposes, and to provide deeper insights into scheduling necessary battery operation management. Three locations were selected from hot, temperate and cold climate regions, and both summer and winter seasonal temperature ranges were considered for the simulation and analysis.